(untitled) (Research, Society and Development, 2022)
The present work seeks to describe the aspects that assert the condition of intestinal dysbiosis and, consequently, the onset of depression and how intestinal modulation can collaborate to improve the quality of life of patients. The possibility of deepening this study collaborates with research aimed at reducing the impacts of microbiota imbalance in the relationship between the gut-brain axis. The methodology consists of a systematic review of data collections, based on bibliographic research, in the production published in LILACS, PubMed and Google Scholar. Studies indicate that the use of probiotics and synbiotics in a prolonged way can positively affect mood, the phenotype related to anxiety and depression, modulate the hypothalamic-pituitary-adrenal axis, alter brain activity and increase the inhibitory neurotransmitter GABA, thus reducing symptoms of depression. anxiety and depression. However, there is a need for further studies to better control the variables (diet, exercise, degree of depression). n this way, this scientific approach highlights a way for society to face disorders related to the brain and intestine, highlighting that modulatory strategies can considerably help to improve the quality of life of patients affected by depression.